Kode Etik sebagai Pilar Penguatan Integritas dan Profesionalisme dalam Pendidikan - Bombom Panjaitan; Dorlan Naibaho (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The teacher code of ethics functions as an important guideline for maintaining integrity and professionalism in the world of education. This article reviews the role of teachers' codes of ethics as a basis for strengthening the values ​​of integrity and professionalism in the modern era. Through a qualitative approach based on literature review, it was found that the teacher code of ethics not only functions as a behavioral guide, but also as a tool for creating a dignified educational environment. However, challenges in implementation, such as lack of understanding and inconsistent implementation, still require serious attention. This article suggests regular training for teachers as well as strengthening ethical oversight by educational institutions.